Protocol to study phagocytosis of apoptotic murine splenocytes by syngeneic antigen-presenting cells in vitro - Lukas M. Braun; Robert Zeiser (STAR Protocols)
Summary: Extracorporeal photopheresis (ECP) effectively reduces immune checkpoint inhibitor (ICI)-induced colitis and is based on the phagocytic uptake of apoptotic ECP-treated splenocytes. Here, we present a flow cytometry-based assay to investigate phagocytosis of ECP-treated murine splenocytes by bone marrow-derived macrophages and dendritic cells in vitro using a congenic marker only present in donor animals and fluorescence labeling of ECP-treated cells. We describe steps for analyzing M2-like polarization markers, investigating protein phosphorylation, and analyzing specific target gene expression in single cells.For complete details on the use and execution of this protocol, please refer to Braun et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.